Evaluation of changes in corneal endothelial morphology during the progression of pterygium by specular microscopy - Songur, Murat Serkan; Erkan, Eyüp; Aslan, Seray; Bayhan, Hasan Ali (Journal of Surgery and Medicine, 2021)
Background/Aim: Corneal endothelial morphology may be corrupted due to pterygium progression. To the best of our knowledge, no study in the literature investigates this. We aimed to evaluate corneal endothelial morphology using specular microscopy (SM) in patients with pterygium. Methods: In this case-control study, we included thirty-three Type 1 pterygium, thirty-one Type 2 pterygium, thirty Type 3 pterygium patients, and thirty healthy controls. The corneal endothelia of all patients were evaluated by SM, and cell density (CD), hexagonal cell ratio (HEX), corneal thickness (CT), and coefficient of variation (CV) were noted. Results: While there was no significant difference in corneal thickness (P=0.480) and coefficient of variation (P=0.068) between the groups in SM images, both corneal endothelial cell count (P=0.003) and hexagonal cell ratio (P=0.002) were significantly lower in Type 2 and Type 3 pterygium patients compared to Type 1 and control groups. Discussion: Corneal endothelial morphology was severely affected in type 2 and 3 pterygium. We think that type 2 and type 3 pterygium patients should be operated on as soon as they are diagnosed to prevent deterioration in corneal endothelial parameters.